2023
DOI: 10.1002/hsr2.1234
|View full text |Cite
|
Sign up to set email alerts
|

Viral etiology of lower respiratory tract infections in adults in the pre‐COVID‐19 pandemic era: A cross‐sectional study in a single center experience from Cameroon

Abstract: Background and Aims: Respiratory viruses are responsible for the majority of lower respiratory tract infections (LRTIs) worldwide. However, there is a gap on the epidemiology of viral LRTIs in adults in sub-Saharan African countries. In Cameroon, like in other countries, the role of viral respiratory pathogens in the etiology of LRTIs in adults is helpful for clinical management. This study aimed to determine the viral aetiologies of LRTIs among hospitalized adults in a reference center for respiratory disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…The overall prevalence however varied according to the age groups, and in the current study, children below 12 months of age and preschool‐age children 1–4 years of age were the most affected. This trend was also supported by a study in Cameron among adults, which reported a low prevalence of 25% [ 29 ]. A study conducted among children below 5 years of age reported much higher prevalence with nearly 83% although this included influenza infections [ 30 ].…”
Section: Discussionsupporting
confidence: 70%
“…The overall prevalence however varied according to the age groups, and in the current study, children below 12 months of age and preschool‐age children 1–4 years of age were the most affected. This trend was also supported by a study in Cameron among adults, which reported a low prevalence of 25% [ 29 ]. A study conducted among children below 5 years of age reported much higher prevalence with nearly 83% although this included influenza infections [ 30 ].…”
Section: Discussionsupporting
confidence: 70%